Discrete element modelling of geogrid-reinforced railway ballast and track transition zones - Chen, Cheng (2013)
Track deterioration has a serious influence on the safety and efficiency (speed restriction) of train operations. Many expensive, disruptive and frequent repair operations are often required to maintain the ballast characteristics due to the problem of settlement. Because of this, a geogrid solution that has proved to be a simple and economical method of reinforcing track ballast is widely used.